[The effect of genetic environment on locus-specific instability of the yellow gene in Uman' population of Drosophila melanogaster] - Zakharenko, L.P.; Voloshina, M.A.; Zakharov, I.K. (Genetika, 2007)
The effects of genotype of the laboratory strains, C(1)DX, ywf/Y, 23.5 MRF/CyL4, and C(1)DX,yf; pi2, on locus-specific instability in the yellow gene of the strains y(2-717, y(2-715), and y(2-700 ) from Uman' population of Drosophila melanogaster was studied. Crosses of the males from Uman'-derived lines with the C(1)DX, ywf/Y females yielded a cascade of derivatives, mostly consisting of y+ and y2 alleles, while their crosses with the 23.5 MRF/CyL4 and C(1)DX,yf; pi2 females mostly resulted in the appearance of y+ and y(1) derivatives. The genomes of laboratory strains used in the study contained the full-sized hobo elements, which could differ from one another relative to the structure of variable region and affinity to different DNA sequences.